Role of Na+, K+-ATPase ion pump in osteoinduction. (15th July 2021) - Tang, Zhurong; Chen, Siyu; Ni, Yilu; Zhao, Rui; Zhu, Xiangdong; Yang, Xiao; Zhang, Xingdong
Abstract: Porous biphasic calcium phosphate bioceramic (BCP) possesses osteoinductivity to induce the osteoblastic commitment of mesenchymal stem cells (MSCs) and ectopic bone formation. However, the underlying mechanism remains enigmatic. We performed a gene array analysis of MSCs cocultured with BCP to screen for candidate osteoinductive modulators. Na +, K + -ATPase (NKA), an ion transporter, therefore was identified as a crucial ion transporter in regulating the osteogenesis of the cells. NKA activator, a polyclonal antibody, enriched the cytomembrane abundance of NKA and lead to an enhanced osteogenic effect of BCP. As indicated in gene array analysis and suggested by co-immunoprecipitation assay, protein phosphatase 2A (PP2A) was elevated by BCP to dephosphorylate NKA and prevent its endocytosis. The inhibition of NKA by ouabain resulted in an adverse effect on osteoinductivity of BCP. We further altered NKA activity in mice implanted with BCP and found that the intensity and incidence of osteoinduction was increased by the NKA activator. We went one step further by investigating the potential of targeting NKA in osteoporotic bone regeneration. Activating NKA upregulated osteogenic gene expression and calcium deposition ability of osteoporotic osteoblasts. Furthermore, activation of NKA in mice ameliorated estrogen-deficiency induced bone loss, in terms of increased bone mass and improved bending strength. With this osteoinductive bioceramic derived ion transporter target, we demonstrate that the activation of NKA has significant potential to revolutionize the regeneration of bone. Statement of significance: In this study, we identified an important role of Na +, K + -ATPase (NKA) have played in osteoinductivity of biphasic calcium phosphate bioceramic (BCP). Furthermore, we demonstrated the therapeutic potential of targeting NKA in osteoporotic bone regeneration. Numerous gene and protein targets to treat osteoporosis were discovered every year, mainly obtained by genomic and proteomic screenings of a large population. In contrast, our study identified an unrevealed bone regenerating target from the upregulated genes induced by an osteoinductive biomaterial. The approach was cost-saving since it did not require a large sample pool. Furthermore, the target derived from this approach was proven to be anabolic. Identification of an anabolic agent holds significant value since most of the current anti-osteoporotic therapies are antiresorptive. Graphical abstract: Image, graphical abstract